Rationale of Assigning Assignments in Bachelor Degree: Opportunities, Challenges and Implementation Strategies Applied by English Language Teachers - Timilsina, Pusparaj (Kalika Journal of Multidisciplinary Studies, 2025)
Although assignments play a crucial role in university education, there is limited knowledge about how university teachers in Nepal oversee the challenges of assigning tasks. This research paper investigates English language teachers’ perspectives on assigning tasks in Bachelor’s Degree programs at community campuses in Pokhara. This study aims to evaluate teachers’ views on assigning tasks and to explore the importance they place on implementing assignments at this level. A mixed-method approach, incorporating both qualitative and quantitative data, was employed. Data were collected using a purposive sampling strategy, with a questionnaire serving as the primary tool for gathering information. Jean Piaget and Lev Vygotsky’s concept of constructivist learning theory is employed to analyze the data of this research. Assignments encourage active knowledge construction, which enhances creativity and critical thinking among students. This theoretical framework can help analyze how assignments are perceived by teachers as tools for fostering critical thinking and deeper understanding of the subject matter. Assignments enable teachers to gauge students’ learning levels and assess their performance, fostering confidence in oral presentations or written exams. Feedback from teachers allows students to address areas for improvement, and their completed assignments reflect their understanding and areas needing further effort. However, students often fail to take assignments seriously, as pass marks are typically awarded regardless of effort despite the acknowledged role of assignments in promoting critical thinking. Overall, assignments valuable for teachers in evaluating students and for students in deepening their understanding of the subject matter